THE QUESTION OF SPEECH GENRES AND OATHS IN BRANCHES OF LINGUISTICS (Scientific journal of the Fergana State University, 2023)
In the article, as a result of the development of the language, the emergence of a second paradigm instead of one scientific paradigm, the emergence of communicative linguistics, which studies the functioning of the language in connection with the process of communication, is the result of the exchange of the system-structural paradigm, which was the leader in the 20th century linguistics, with the anthropocentric paradigm, and At the current stage of development of linguistics, the priority of looking at language elements from an anthropocentric point of view and evaluating them based on the relationship between "language and its owner" is stated.